PENGARUH EFEKTIVITAS PENGENDALIAN ANGGARAN, IKLIM KERJA ETIS, PARTISIPASI ANGGARAN DAN PERSEPSI KEADILAN PROSEDURAL TERHADAP KECENDERUNGN MENCIPTAKAN SENJANGAN ANGGARAN PADA PERUSAHAAN MANUFAKTUR DI KABUPATEN SERANG - Devi, Deasy Femayona (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
This study examines the effect of budget participation, budget goal commitment, job satisfaction and managerial performance. This study uses a manufacturing company located in the district of Serangsebagai object of research. The number of samples in this study were 60 respondents. Data were analyzed by using SEM (Structural Equation Model) through the program SmartPLS (Partial Least Square) version 1.0. The results of this study states the effectiveness of budgetary control effect on the perception of procedural fairness. The effectiveness of budgetary control affect the propensity create budgetary slack. Participation budget affect the perception of procedural fairness. Ethical work climate influence the perception of procedural fairness. Ethical work climate does not affect the tendency to create budgetary slack. Perceptions of procedural justice affect the tendency to create budgetary slack. For manufacturing companies is expected to be used as a tool for evaluation and improvement  of  performance. For further research  is expected  to add  variable  external factors (job satisfaction, motivation, etc.) and add to the respondent. Researchers are also expected to develop further the research of various other business entities, such as the banking sector, hospitality, service, commercial or state-owned